Inovasi Program Sosialisasi Anti-Bullying dan Pencegahan Kekerasan Seksual oleh Kelompok Kukerta Desa Sipungguk sebagai Upaya Mewujudkan Tujuan Pembangunan Berkelanjutan (SDGs) - Farhan Rizki Vermana; Separen Separen; Raja Siti Jalilah Nafisah; Naila Nafisa Zulfikar; Nazwa Syaidini; Hayat Yulanda; Faiqah Kania; Dimas Maulana Rasyidi; Mhd Aidil Ichwan; Nabila Rinaldi; Fazl Mawla Dini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The anti-bullying and sexual violence prevention program carried out by community service students (Kukerta) in Sipungguk Village aims to increase community and student literacy on violence issues while supporting the achievement of the Sustainable Development Goals (SDGs). The method applied was a community-based educational approach through participatory strategies such as poster installation, educational video screening, interactive discussions, and role-playing simulations. The program targeted elementary school students with age-appropriate materials. The results indicate an improvement in students’ understanding of bullying and sexual violence, including prevention measures. Furthermore, the program created a safe space for children to share experiences, foster empathy, and build courage to report incidents. This initiative aligns with SDG 4 (quality education), SDG 5 (gender equality), and SDG 16 (peace, justice, and strong institutions). The conclusion highlights that the combination of legal education and community empowerment provides a concrete contribution to developing a safe, inclusive, and sustainable social environment.